2022-VA-1138-ESGO Laparoscopic anterior resection with total vaginectomy. (20th October 2022) - Raju K, VVN; Jonnada, Pavan kumar; Usofi, Zeeba; Madhu, B; Pradeep, K; Nusrath, Syed
Abstract : Introduction/Background: This is a video demonstration of laparoscopic anterior exenteration with total vaginectomy for vaginal squamous cell cancer in a young female. Methodology: Techniques of dissection and surgical demonstration of anterior exenteration with total vaginectomy Results: Video demonstrated in the given format Conclusion laparoscopic anterior exenteration with total vaginectomy is an acceptable surgical procedure with minimal morbidity for the management of locally advanced vaginal cancer.